Regulation of cell behaviour by plant receptor kinases: Pattern recognition receptors as prototypical models - Albert, Markus; Jehle, Anna K.; Lipschis, Martin; Mueller, Katharina; Zeng, Yi; Felix, Georg (European Journal of Cell Biology, 2010)
In this review we focus on pattern recognition receptors in plants that detect extracellular signals indicative for pathogen attack and injury. We start out with a discussion on FLS2, which binds and responds to bacterial flagellin, and then concentrate on ligand-receptor interactions as initial steps in the molecular receptor activation process. Comparison with other receptor kinases, whether involved in plant immunity or regulation of other cellular programs, might indicate common principles of receptor activation. © 2009 Elsevier GmbH.
CRIS-Team Scopus Importer:2020-03-09
Keywords: Address-message concept; Microbe-associated molecular patterns; Pattern recognition receptors; Plant; Receptor-like kinases